2018
DOI: 10.1093/jas/sky406
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in cattle crossbreeding schemes in tropical regions: meta-analysis of effects of breed combination, trait type, and climate on level of heterosis1

Abstract: The aim of this study was to investigate the effects of animal trait, breed combination, and climate on the expressed levels of heterosis in crossbreeding schemes using tropical cattle. A meta-analysis of 42 studies was carried out with 518 heterosis estimates. In total, 62.5% of estimates were found to be significantly different from zero, the majority of which (89.8%) were beneficial for the studied trait. Trait and breed combination were shown to have a significant effect on the size of heterosis (P < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
27
1
2
Order By: Relevance
“…According to Yakubu and Ibrahim (2011), phenotypic distance measures can be used as a baseline for designing a breeding program of the population. Breeding processes between livestock animals with high phenotypic distances may yield appreciable heterosis concerning most economic traits (Bunning et al 2019). Crossing individuals from distant populations will enhance variability compared to crossing individuals from tightly connected populations.…”
Section: Phenotypic Relationships Between Indigenous Buffaloes From Bmentioning
confidence: 99%
“…According to Yakubu and Ibrahim (2011), phenotypic distance measures can be used as a baseline for designing a breeding program of the population. Breeding processes between livestock animals with high phenotypic distances may yield appreciable heterosis concerning most economic traits (Bunning et al 2019). Crossing individuals from distant populations will enhance variability compared to crossing individuals from tightly connected populations.…”
Section: Phenotypic Relationships Between Indigenous Buffaloes From Bmentioning
confidence: 99%
“…Similarly, taurine-indicine heterosis effects were found to be significant for estimates of growth curve parameters, total milk yield, calf weaning weight, predicted energy intake by cows and cow efficiency, and greater than those for taurine breed crosses (Mendonça et al, 2019). However, an even greater benefit of heterosis was observed expressed in crosses of breeds adapted to different environments (Bunning et al, 2019). Because the Sanga cattle breeds are likely to be composites between Bos taurus and Bos indicus (Hanotte et al, 2002;Makina et al, 2016), this may in part explain their adaption to the South African environment.…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, compromised reproductive performance of crossbred animals is a major constraint faced by the farmers in these countries. Studies conducted on crossbreeding schemes in tropical regions revealed that milk production showed higher (35.13%) heterosis but fertility showed only moderate (12.02%) heterosis ( Bunning et al, 2019 ). Since the focus was on milk production, reproduction was frequently overlooked, with the result that infertility problems in crossbred cattle persist.…”
Section: Introductionmentioning
confidence: 99%